In search of excellence - Nathan, John.; Peters, Thomas J.; Exel/Media (Firm). (Washington, DC : PBS Video, 1985)
A documentary, shot on location, which examines examples of successful management in large and small companies. Focuses on the three major themes of innovation, productivity through people, and shared values, and tells how companies have benefited from their use.
Backup available in VHS 1/2 in.
Keywords: Peters, Thomas J; Industrial management -- United States -- Case studies; Industrial management -- United States; Industrial management